2021
DOI: 10.1111/dom.14518
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of iGlarLixi versus IDegAsp: Results of a systematic literature review and indirect treatment comparison

Abstract: Aim: To assess the efficacy and safety of iGlarLixi, a fixed-ratio combination of basal insulin glargine 100 U/mL and lixisenatide (glucagon-like peptide-1 receptor agonist) versus IDegAsp, a co-formulation of basal insulin degludec 100 U/mL with rapidacting insulin aspart. Materials and Methods:A systematic literature search of randomized controlled trials (RCTs) was performed. Outcomes from eligible RCTs were compared by an indirect treatment comparison using a Bayesian framework. Subanalyses of Japanese and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Furthermore, the present analysis results are consistent with the findings of a systematic literature review and indirect treatment comparison, comparing the efficacy and safety of iGlarLixi versus premix IDegAsp 21 . The MD in HbA1c change with iGlarLixi was statistically higher versus IDegAsp {MD = −0.64 [95% credible interval (CrI): −1.01, −0.28] %units}.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Furthermore, the present analysis results are consistent with the findings of a systematic literature review and indirect treatment comparison, comparing the efficacy and safety of iGlarLixi versus premix IDegAsp 21 . The MD in HbA1c change with iGlarLixi was statistically higher versus IDegAsp {MD = −0.64 [95% credible interval (CrI): −1.01, −0.28] %units}.…”
Section: Discussionsupporting
confidence: 88%
“…20 Furthermore, the present analysis results are consistent with the findings of a systematic literature review and indirect treatment comparison, comparing the efficacy and safety of iGlarLixi versus premix IDegAsp. 21 The MD in HbA1c change with iGlarLixi was statistically In previous studies, iGlarLixi has been shown to provide improved glycaemic control while attenuating insulin-related body weight gain and having a similar risk of hypoglycaemia versus iGlar alone. 14,15 A meta-analysis of randomized controlled trials comparing basal insulin with twice-daily or thrice-daily premix insulin showed that while premix insulin provided improved glycaemic control, it was also associated with higher risk of hypoglycaemia and increased weight gain.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11][12][13][14] Moreover, FRCs have also been shown to be more effective at achieving glycaemic control, with greater satisfaction versus basalbolus insulin and their individual components. [15][16][17] However, data comparing the two available FRCs for hard clinical endpoints are lacking. 11 In a large cardiovascular outcome trial, few differences were found between insulin degludec and insulin glargine, although fasting glucose, severe hypoglycaemia, and nocturnal severe hypoglycaemia favoured insulin degludec.…”
Section: Introductionmentioning
confidence: 99%
“…Bodyweight change was more favourable for iGlarLixi, however, the comparisons of hypoglycemia were inconclusive owing to differences in definitions between studies. AEs were more frequent with iGlarLixi because of GI intolerance [ 59 ].…”
Section: Discussionmentioning
confidence: 99%